Análisis comparativo de la eficiencia de colectores solares témicos y colectores solares termodinámicos utilizados en bombas de calor asistidas por energía solar para la generación de agua caliente en el sector residencial - Otavalo Catucuamba, Tania Ivon (2018)
This research project shows an in-depth analysis as well an evaluation of two solar collector technologies commonly used in heating systems. The studied technologies are flat-plate solar collectors and thermodynamic panels with solar- assisted heat pump. For the purpose of this project, both technologies were tested in their major application, sanitary water heating which represented near to 80% of thermal energy market for the residential sector in 2013. As a part of the tests done, each kind of solar collectors was heated around 30 minutes for every one pump’s cycles in order to gather some experimental data as environment temperature besides minimum and maximum solar irradiation. To illustrate, the average temperature measured during a clear day was 23° C meanwhile the maximum solar irradiation was 803.3 W/m2. Under these weather conditions, water reached a temperature of 58.9° C for the flat-plate collector. In the other hand, water reached 41.91° C for the thermodynamic collector, yet the maximum solar irradiation was 1074 W/m2 in this essay. Another important element evaluated in the tests is the useful heat that is the heat gained inside of the collectors. The results for this parameter were 568.22 W for the first kind of collectors and 89.66 W for the second one in a clear day. Finally, all the analyzed elements and parameters help to achieve the efficiency of every collector and determine the best system which can be installed with the heat pump.